A retrospective study on bovine fascioliasis in Veterinary Regional Laboratories in Peninsular Malaysia - Md Isa, Nur Mahiza; Kamaludeen, Juriah; Busayo, Ibitoye E.; Hassan, Latiffah; Jamaludin, Nur Alia Diyana; Idris, Lokman Hakim; Saulol Hamid, Nur Fazila; H., Noor Hazfalinda; Chandrawathani, P. (Hindawi Publishing, 2019)
This is a retrospective study on bovine fascioliasis infection on cattle in Peninsular Malaysia, spanning from January 2007 to December 2017. Cattle were diagnosed with Fasciola based on the fecal examination and the results were reported to the Veterinary Regional Laboratories in Peninsular Malaysia. These records were analysed for the occurrence of bovine fascioliasis within that 11-year period. Records of annual diagnostic cases from five major Veterinary Regional Laboratories were examined: Bukit Tengah, Pulau Pinang (north); Kuantan, Pahang (east); Johor Bahru, Johor (south); Sepang, Selangor (west); and Kota Bharu, Kelantan (east). A positive fascioliasis infestation was calculated based on a number of positively infected cattle with Fasciola from a number of cattle examined. A total of 1988 cattle were examined during this period and 35 (1.76%) cattle were reported to be positive for bovine fascioliasis. Parasite infection was the highest at Bukit Tengah region (5.55%) where 19 cases were positive from 342 reported cases while, at Kuantan (4.96%), 15 positive cases were reported, unlike Johor Bahru (0.09%), with only 1 positive case from 1136 cattle examined. Sepang and Kelantan had no positive cases. These results showed that bovine fascioliasis was generally prevalent in the northern and southeast parts of the Peninsular Malaysia; however, there was no significant relationship between the region and the occurrence of fascioliasis.